Red cell distribution width (RDW) and neutrophil-to-lymphocyte ratio (NLR) as predictors of outcome in acute pancreatitis (Journal of Bangladesh College of Physicians and Surgeons, 2024)
BACKGROUNDAcute pancreatitis is a commonly encountered emergency in children. It has always been tough to predict accurately among the patients who will become systemically unwell. Simple prognostic markers, such as red cell distribution width (RDW) and neutrophil-to-lymphocyte ratio (NLR), could identify such patients. This study was done to assess the usefulness of those markers.METHODSThis cross-sectional study was conducted from July 2018 to June 2020 at department of Pediatric Gastroenterology and Nutrition, BSMMU, Dhaka. Thirty-one children with abdominal pain diagnosed as acute pancreatitis were included by purposive sampling in the study.RESULTSThe mean age of the pediatric patients was 11.19 (±3.45) years. The mean red cell distribution width was 14.99 (±2.96) and mean neutrophil-to-lymphocyte ratio was 4.49 (±3.99). Total thirty patients (97%) were recovered and one patient (3%) died in hospital stay. Thirteen patients (41.9%) developed complications among which ascites was more common (12, 38.7%). NLR> 5 was observed in higher proportion in the study subjects with complications (46.2%) than without complications (16.7%) without any statistically significant difference. RDW ≥14 was found in 53.8% study subjects with complications and 50% without complications. However, no statistically significant difference was found. Length of hospital stay was longer in patients with NLR >5 than with NLR ≤5. RDW